2015
DOI: 10.1108/ics-02-2013-0009
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effectiveness of phishing filters against DNS based phishing attacks

Abstract: Purpose -This paper aims to report on research that tests the effectiveness of anti-phishing tools in detecting phishing attacks by conducting some real-time experiments using freshly hosted phishing sites. Almost all modern-day Web browsers and antivirus programs provide security indicators to mitigate the widespread problem of phishing on the Internet. Design/methodology/approach -The current work examines and evaluates the effectiveness of five popular Web browsers, two third-party phishing toolbar add-ons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…In short, the related studies in Zhang et al (2007a), Sheng et al (2009) and Purkait (2015) have raised critical concerns on the reliability of the conventional tools. Furthermore, the existing tools also face challenges from increasingly sophisticated…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 1 more Smart Citation
“…In short, the related studies in Zhang et al (2007a), Sheng et al (2009) and Purkait (2015) have raised critical concerns on the reliability of the conventional tools. Furthermore, the existing tools also face challenges from increasingly sophisticated…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…Recently, Purkait (2015) tested the latest commercial browsers and security applications, where 12 out of 14 tools have failed to detect any of the phishing websites that existed for only a few minutes old. In short, the related studies in Zhang et al (2007a), Sheng et al (2009) and Purkait (2015) have raised critical concerns on the reliability of the conventional tools.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…They examined 10 antiphishing tools and discovered that only one of them could consistently detect more than 60% of the phishing websites tested. Their conclusion is echoed by another study from Purkait (2015), who examined the latest commercial browsers and showed that 12 out of 14 tools failed.…”
Section: Related Studies On Identifying Malicious Attacksmentioning
confidence: 98%
“…Although it is very straightforward and has been widely used in different browser toolbars, some studies have confirmed the ineffectiveness of such techniques (e.g. Tsai et al , 2011; Purkait, 2015). The main reason being it is not only challenging but also almost impractical for any blacklist to be up-to-date all the time (Ma et al , 2009a, b; Pranata et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation